Integrating VR in Communication Practices: A Multisectoral Narrative Review with Emphasis on Education, Healthcare, and Marketing in Global Contexts - Pratama, Alfian; Patrissia, Ressa Uli (Indonesian Scientific Publication, 2024)
The integration of Virtual Reality (VR) and immersive technologies in communication is reshaping how individuals engage, interact, and learn across various sectors. This narrative review explores the applications and challenges of VR in education, healthcare, marketing, and cultural heritage communication. The study aimed to analyze current literature to uncover the transformative potential and limitations of VR-based communication practices. The review utilized a comprehensive literature search in databases such as Scopus, PubMed, and Google Scholar using keywords including